Clinical profile and prognostic indicators of neurotoxic snake bite in rural India - Hassan, Suhail; Saini, Rijul; Aggarwal, Monuj (International Journal of Advances in Medicine, 2019)
Background: In rural India, snakebite is an occupational and environmental hazard. WHO listed snakebite as one of the neglected tropical diseases and in rural India it is underreported because of popular traditional methods of treatments and lack of healthcare facilities. This study is an attempt to look into the epidemiological, clinical and prognostic indicators of neurotoxic snake bite in rural India. Methods: This study is a prospective, descriptive study of 25 neurotoxic snake bites admitted in our hospital from January to September 2019. Clinical factors like age, sex, clinical features, management and the outcome of patients are studied. Results: Young males were common victims of snakebite in evening hours during monsoon season. All patients received traditional methods of treatment, and despite this 64% of our patients reported to the hospital within 6 hours after the bite. Overall, the mortality rate in this study was 12%. Poor outcome was also noted in cases who were having respiratory failure and needed artificial ventilation (30%). Mortality was 22.2% in patients where bite to admission time was greater than 6 hours as compared to 6.25% in patients where it was less than 6 hours. Conclusions: Author concluded that a neurotoxic snake bite is a life-threatening emergency. In preventive measures, outdoor activities in dim lights during monsoon season should be restricted. Traditional treatments are still popular and trusted methods of treatment in rural India and these healers can be educated to recognize and refer immediately all neurotoxic bites to nearby medical facilities.